Assessing Population Invariance of 2021 Agricultural Science Examination of National Examination Council (NECO) in North Central Nigeria - Omale, Onuh; Obinne A. D. E.; Aduloju M. O.; Emaikwu S. O. (Journal of Research in Science and Mathematics Education, 2024)
Purpose: This study examines the challenges and implications of equating scores from different test forms, focusing on the 2021 NECO Agricultural Science examinations in North Central Nigeria. It considers factors such as school location, school type (public vs. private), and test administration (internal vs. external) to evaluate the extent to which these equated scores maintain invariance across different populations. Methodology: The study employs a non-equivalent anchor test (NEAT) group equating design and analyzes data from a population of 97,413 Senior Secondary students using the IRT statistical tool. Findings: The key findings reveal significant disparities in the equated scores between internal and external examinations, as well as between urban and rural locations. These discrepancies challenge the fairness and comparability of the examinations, raising concerns about potential biases and inequities in educational assessment. Significance: The research highlights the importance of achieving population invariance in test equating methodologies. It recommends adopting efficient equating methods, such as mean equating, and utilizing the Item Response Theory (IRT) approach for standardized test development to ensure fairness and equity in educational evaluations.